Using nexus tools to evaluate water, energy, food, and ecosystems policies in the Ganges Basin, India. - Singh, Vartika; Alam, Mohammad Faiz; Sharma, Ruchi (International Water Management Institute, 2024)
A review of policies and programs on water, energy, food, and ecosystems in India showed that multiple policies have been enacted; however, these policies rarely consider the impact on other sectors, and associated programs significantly overlap in terms of objectives and goals. For this reason, since 2022, NEXUS Gains has developed methodologies and tools to enable the assessment of WEFE policy scenarios for synergistic action in India.